(untitled) (Transport systems and technologies, 2021)
The article considers the reliability and protection of information of computer systems of transport infrastructure and describes the synthesis and analysis of differential game models and methods of modeling cyberattack processes on the server of computer information and diagnostic systems of the railway power supply distance. A unified differential-game model of the cyberattack process on the multi-task server of the information-diagnostic computer system of the lower level of the railway has been developed, which allows to obtain optimal strategies for information protection in cyberattacks. The results of modeling the cyberattack process are presented, to assess the integrated indicators of server security, using the optimal strategies for each of the functions. The appearance of the unified model of the computer information system is shown, and the graphs of the transient processes of the probability of the server being in a protected state and the probability of server failure for any of the functionalities are given.